Association between increased serum thyrotropin concentration and the oldest old: what do we know? - Glaucia Cruzes Duarte; Maysa Seabra Cendoroglo; Lara Miguel Quirino Araújo; Clineu de Mello Almada Filho (Einstein (São Paulo))
To assess studies that evaluate the relation between serum thyrotropin concentration, very old subjects, and their events. We searched the PubMed, SciELO, and LILACS databases for articles published between 2004 and 2012. Our search was restricted to studies involving humans aged 65 years or older, and written in English, Spanish, or Portuguese. Studies that evaluated the association between elevated serum thyrotropin concentration among elderly subjects with subclinical hypothyroidism were chosen since at least in part they included a subpopulation of individuals aged 80 years and above. Thirteen studies were selected. No significant increase in risk of cardiovascular events, coronary heart disease, or total mortality was observed. Elevated thyrotropin concentration was associated with longevity. More randomized controlled trials are required to better define the potential benefits of elevated thyrotropin concentration in this oldest old population, hormone replacement, and longevity.